2021
DOI: 10.1111/ner.13234
|View full text |Cite
|
Sign up to set email alerts
|

Directional Deep Brain Stimulation of the Thalamic Ventral Intermediate Area for Essential Tremor Increases Therapeutic Window

Abstract: Objectives Deep brain stimulation (DBS) of the posterior subthalamic area (PSA) and the ventral intermediate thalamic nucleus (VIM) is a well‐established therapy for essential tremor (ET), but it is frequently associated with side effects like dysarthria or gait ataxia. Directional DBS (dDBS) may be a way to activate fiber tracts more selectively. Is dDBS for ET superior to omnidirectional DBS (oDBS) regarding therapeutic window and clinically as effective as oDBS? Materials and Methods Ten patients with ET tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
4
25
1
Order By: Relevance
“…Given the fact that for the awake group, TW also seemed to be wider for dDBS but without reaching statistical significance, we cannot rule out that our analysis was underpowered due to smaller sample size in the awake group. However, these results are generally consistent with previous studies which showed a superiority of directional compared to omnidirectional stimulation regarding therapeutic window (7,11,26). Earlier reports have already shown dDBS to increase TW by either decreasing TT or increasing SET, but our study is the first to show both decrease of TT and increase of SET at the same time with the same single segment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Given the fact that for the awake group, TW also seemed to be wider for dDBS but without reaching statistical significance, we cannot rule out that our analysis was underpowered due to smaller sample size in the awake group. However, these results are generally consistent with previous studies which showed a superiority of directional compared to omnidirectional stimulation regarding therapeutic window (7,11,26). Earlier reports have already shown dDBS to increase TW by either decreasing TT or increasing SET, but our study is the first to show both decrease of TT and increase of SET at the same time with the same single segment.…”
Section: Discussionsupporting
confidence: 93%
“…With this new lead design, stimulation is supposed to be delivered more precisely with less effect on adjacent areas (9). Several studies could show that directional deep brain stimulation (dDBS) results in a wider therapeutic window (TW), defined by the stimulation current difference between therapeutic threshold (TT) and side effect threshold (SET), for both subthalamic nucleus (STN)-and VIM-DBS (6,8,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our findings, a recent study by Bruno and co-workers found a small but significant difference between omnidirectional and directional stimulation of the VIM and PSA. ( Bruno et al, 2020 ). Therefore, whether PSA stimulation may ultimately benefit from directional current steering would need to be explored in additional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Current commercial systems typically consist of ring contacts segmented in three sections that can be individually activated, although many other designs have been proposed [69]. Early experience has shown that directional stimulation can increase the therapeutic window while reducing the therapeutic current strength relative to omnidirectional stimulation [70][71][72][73][74]. Whether or not this translates into improved patient outcome remains unclear and might depend on the underlying condition and target.…”
Section: Directional Leadsmentioning
confidence: 99%